Clinical evaluation of aphrodisiac activity of a novel ayurvedic formulation for treatment of male sexual disorders - Gupta, Mradu; Mondal, Asim Kumar (International Journal of Research in Medical Sciences, 2020)
Background: Sida cordifolia Linn. and Glycyrrhiza glabra Linn. have been mentioned in Ayurvedic texts for their anti-inflammatory, antioxidant and sexual properties. After finding good results in treatment of male sexual disorders during pre-clinical studies, this clinical trial was taken up to assess the spermatogenesis action of aqueous extract of roots of these two plants. Methods: The study used qualitative criteria such as primary and secondary symptoms and quantitative investigations such as haematological investigations, hormonal analysis and semen analysis for assessing the therapeutic efficacy of research formulation through placebo controlled clinical trials on 50 males having lack of sexual desire and non-satisfactory sexual life. Results: Very high inhibition was noticed in respect of primary symptoms such as lack of libido, difficulty in ejaculation or little amount of semen, as well as secondary symptoms such as nausea, body ache, headache, indigestion, loss of appetite and general weakness in the research group. Lack of any adverse changes in haematological parameters (blood sugar, haemoglobin, ESR, RBC and WBC) and biochemical parameters (bilirubin, protein, SGPT and SGOT and ALP) indicate the non-toxic nature of research formulation. The hormonal levels registered a significant increase during clinical study in research group, especially the testosterone level (10.36%). Semen quality evaluated through sperm count, motility and morphology showed a significant improvement in research group, suggesting that administration of research drug in cases of stress-related sexual problems protected healthy cells by reduced generation of ROS and helped maintain quality parameters of spermatozoa during spermatogenesis. Conclusions: The research formulation made from roots of Sida cordifolia Linn. and Glycyrrhiza glabra Linn. showed good and significant (p<0.05) therapeutic efficacy through inhibition of primary and secondary symptoms and enhancement in hormonal and seminal parameters, validating its spermatogenesis effect without any toxic or adverse effects.